PERBANDINGAN KADAR TIMBAL (Pb) DARAH YANG DISIMPAN PADA BERBAGAI TABUNG VACUTAINER - Sudarma Nyoman; Ni Wayan Desi Bintari (LPPM Universitas Abdurrab, 2024)
Lead heavy metal (Pb) testing using blood specimens needs to pay attention to the selection of vacutainer tubes. The coagulant content in the vacutainer tube may affect the blood lead metal (Pb) levels examined. The types of vacutainer tubes that are often used in blood lead metal examination are red caps, purple caps, and dark blue caps. The vacutainer tube of the red cap does not contain coagulants while the purple cap contains EDTA coagulant, and the blue cap contains metal-free coagulants. The selection of the right type of vacutainer tube is a pre-analytical stage that affects the results of the examination. This study aims to determine the ratio of blood lead (Pb) levels stored in vacutainer tubes through accuracy tests. This study is an experimental study, which compares blood lead levels stored in the vacutainer tube of red, purple, yellow, and dark blue caps. The comparison is analyzed based on the validation of percent recovery. Each blood sample in the vacutainer tube was wet destroyed, and lead level analysis was performed with an Atomic Absorption Spectrophotometer (SSA) with internal standard additions. Based on the results obtained, the percentage of recovery in red, purple, dark blue and yellow cap vacutainer tubes was 110%, 36.33%, 110%, and 21.6%, respectively. A good percentage of recovery is in the range of 80% - 110% so it can be concluded that the vacutainer tube of the red cap and dark blue cap has a lead content with a good percentage of recovery of 110%.